Päätöksentekijöiden viiteryhmät kaupunkien liikuntapolitiikassa - Olin, Kalevi (1982)
The purpose of the present study was to determine how the sport political decision-makers acted while making decisions, and which reference groups and backgrounds they selected as support for their decision-making behavior. A sample of 700 was selected from a population of 1,162 general officials (city mayors, associate mayors, and administrative secretaries), special officials ( city planners and leading sport officials), and appointed representatives ( members of the sport bodies). The results indicated that the following reference groups, listed in order of descending importance, were most often chosen as support by the majority of the decision-makers: the city officials preparing the decision issues, colleagues at one's place of work, top athletes, participants in mass sports, leaders of sport clubs, and the members of the city council belonging to one's own party. Generally, the minority turned to the more distant backgrounds for support, e.g. to the sport political ideologies of the political parties and the central sport organizations. This was the case also with the local school teachers of physical education. Political affiliation and the role in the decision-making process explained most of the variance on the individual level. On the collective level, the behavioral differences were clearly smaller, and mostly related to the political climate of the city.